FRI0009 CD4+ T helper cells in rheumatoid arthritis express high levels of interleukin-21. (23rd January 2014) - Lebre, M.C.; Vieira, P.L.; Aarrass, S.; Newsom-Davis, T.; Tak, P.P.; Screaton, G.R.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting synovial tissue in multiple joints. The inflammatory process in RA is regulated by several cytokines, especially TNF, which is produced not only by macrophages and dendritic cells (DC) but also by activated antigen-specific CD4 + T helper (Th) cells. IL-21 is a pleiotropic type 1 cytokine that shares the common cytokine receptor γ-chain, γ(c), with IL-2, IL-4, IL-7, IL-9, and IL-15. IL-21 promotes differentiation of Th17 cells and is implicated in several autoimmune diseases, including type 1 diabetes, systemic lupus erythematosus and RA. Recently it was shown that this inflammatory cytokine is secreted by T follicular helper cells (TFh). IL-21 regulates antibody production by B cells and induces osteoclastogenesis, mechanisms that contribute to RA pathology. In addition, administration of an IL-21R fusion protein to mice after the onset of arthritis reduced both the clinical and histological signs of collagen-induced arthritis. Objectives: Taking into account the recent literature we investigated whether IL-21 might play a role in RA. Methods: Expression of surface markers and cytokine production at the single cell level in peripheral blood (PB) and matched synovial fluid (SF) from RA (n=10) and psoriatic arthritis (PsA, n=7) patients, as compared to PB of healthy control (HC) subjects (n=25), was evaluated by flow cytometry following polyclonal stimulation ex-vivo. IL-21 concentrations were assessed by ELISA in cell-free SF samples of RA (n=15), PsA (n=14) and OA (n=5) patients and in 6 days supernatants of RA (n=6) and spondyloarthropathy (SpA, n=5) synovial biopsy cultures. Immunohistochemistry analysis was performed on synovial tissues (STs) of HD, RA, PsA and OA patients and sections were evaluated by digital image analysis. In addition we dissected the in vitro requirements for the differentiation of human IL-21-secreting CD4+ T helper (Th) cells from naïve T cells. Results: We observed significant expansions of CD4+ Th cells secreting IL-21 in RA SF compared to matched PB (p=0.0005). Interestingly, while the % of IL-21+ CD4 in PB did not differ between RA, PsA and HC, the % of IL-21+ CD4 in RA SF was increased compared to PsA. In addition, the levels of IL-21 present in SF did not differ between RA and PsA but there was trend towards elevated levels of this cytokine in RA SF compared to OA SF (p=0.067). In ST, IL-21 expression in RA patients was significantly higher compared to HD (p=0.04). RA synovial biopsies released significantly higher levels of IL-21 compared to SpA. CD4 + IL-21 + could be detected in RA ST that do not co-localized with IL-17 neither IL-22. Synovial IL-21-secreting cells did not phenotypically fit the TFh cell paradigm in that they did not express CXCR5. In humans, differentiation of naïve CD4 + T cells into IL-21-secreting cells in vitro was preferentially driven by IL-21 and/or IL-6 in the additional presence of transforming growth factor-β. Conclusions: IL-21 and IL-21 blocking therapy is now being tested in a number of diseases. The results of this study enhance the rationale for a trial of IL-21 blockade in RA. Disclosure of Interest: None Declared